2004
DOI: 10.1038/sj.onc.1207990
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Snail transcription during epithelial to mesenchymal transition of tumor cells

Abstract: Expression of Snail transcriptional factor is a determinant in the acquisition of a mesenchymal phenotype by epithelial tumor cells. However, the regulation of the transcription of this gene is still unknown. We describe here the characterization of a human SNAIL promoter that contains the initiation of transcription and regulates the expression of this gene in tumor cells. This promoter was activated in cell lines in response to agents that induce Snail transcription and the mesenchymal phenotype, as addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
265
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(281 citation statements)
references
References 37 publications
13
265
3
Order By: Relevance
“…Snail1 mRNA expression is also regulated by RAS activation, but to a much lesser extent than Snail2. Snail1 expression has previously been reported to be induced by RAS and transforming growth factor-b (TGF-b) signalling through pathways involving both MAP kinase and PI3-kinase activities (Peinado et al, 2003;Barbera et al, 2004). With the ER:HRAS V12 system in HKe-3 cells, we showed that the Snail1 mRNA level was increased around 2.5-fold with 50 nM OHT after 3 days of induction (Figures 2h and i).…”
Section: Snail2 In Ras Induced Emtmentioning
confidence: 61%
“…Snail1 mRNA expression is also regulated by RAS activation, but to a much lesser extent than Snail2. Snail1 expression has previously been reported to be induced by RAS and transforming growth factor-b (TGF-b) signalling through pathways involving both MAP kinase and PI3-kinase activities (Peinado et al, 2003;Barbera et al, 2004). With the ER:HRAS V12 system in HKe-3 cells, we showed that the Snail1 mRNA level was increased around 2.5-fold with 50 nM OHT after 3 days of induction (Figures 2h and i).…”
Section: Snail2 In Ras Induced Emtmentioning
confidence: 61%
“…Transforming growth factor-b increases Snail expression during hair bud morphogenesis (37), while Notch upregulates Snail during cardiac valve development (38). Studies with cultured cells have identified several intracellular signaling pathways capable of inducing Snail transcription, including the MAPK, phosphoinositide-3-kinase (PI3K), integrinlinked kinase (ILK), and nuclear factor-kB (NFkB) pathways (39)(40)(41)(42). Several transcription factors have been linked to Snail induction, including Gli1 (43), early growth response 1 (EGR1; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factors have been linked to Snail induction, including Gli1 (43), early growth response 1 (EGR1; ref. 44), high mobility group AT-hook 2 (45), and NFkB (40,41). Response elements to some of …”
Section: Discussionmentioning
confidence: 99%
“…In addition, TNF-α-induced cell migration and invasion were associated with NF-κB-mediated stabilization of Snail [3,6] . Because NF-κB may bind to the human Snail promoter causing increased Snail expression [19] , we tested whether the regulation of Snail expression might be involved in the TNF-α-mediated migration and invasion of PC3 cells. A ChIP assay revealed that the NF-κB p65 subunit was constitutively bound to the Snail promoter, and this binding was increased upon NF-κB activation by TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that transcription of Snail was regulated by the NF-κB pathway [6] . As a critical subunit of NF-κB, p65 can bind the human Snail promoter and increase Snail transcription [19] . To further determine the mechanisms underlying the regulatory effect of GA on TNF-α-induced cell invasion, we examined the DNA binding activity of NF-κB using a ChIP assay.…”
Section: Involvement Of the Pi3k/akt Signaling Pathway In Ga-induced mentioning
confidence: 99%